Methods for Lipase Immobilization and Their Use for Biodiesel Production from Vegetable Oil - Yucel, Y.; Demir, C.; Dizge, N.; Keskinler, Bülent (Taylor & Francis Inc, 2014)
In the present work, two different lipases (triacylglycerol hydrolase, EC 3.1.1.3), Lipozyme TL-100L and Novozyme 388, were immobilized onto three different low-cost supports using both adsorption and covalent method: celite 545, silica gel, and styrene-divinylbenzene copolymer. The maximum immobilization yield was obtained as 79.0% for Lipozyme TL-100L and the highest specific activity was 6.5 U/mg protein for Novozym 388. The properties of the support and immobilized derivatives were characterized by Fourier transform infrared spectroscopy. Maximum methyl esters yield was obtained as 98.3%. The lipases, which are immobilized by covalently, proved to be stable after even 10 repeated reuses.
Keywords: lipase immobilization; biodiesel; Novozyme 388; alcoholysis; transesterification; Lipozyme TL-100L